The Role of Sultan Oesman Sadiq Syah in Preserving the Bacan Sultanate’s Legacy (1900-1935 AD) - Atim, Arfandi; Warwefubun, Jamain; Misbahuddin, Misbahuddin (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
This research to analyze the role of Sultan Oesman Sadiq Syah in preserving the heritage of the Bacan Sultanate (1900-1935). The research was conducted to determine the role of Sultan Oesman Sadiq Syah in preserving the Bacan Sultanate’s legacy (1900-1935). The method used is historical research, namely; heuristics, criticism, interpretation, and historiography, using an oral history approach. The data collected is then analyzed and conclude. The results of the research show that: First, the system of government uses an absolute monarchy system, that is, in every ecstasy the Sultan's leadership will be continued by his direct descendants from a son, who in the Bacan Sultanate is known as "Assultan ibnu". sultan”, meaning that the Sultan is the son of the previous sultan. Second, Sultan Oesman Sadiq Syah's contribution to the Bacan Sultanate included the formation of two large communities, intelligent politics/commerce politics, and building the religious, educational and economic centers of the sultanate.